ADVANCED PROPTOSIS AND HYPERTELORISM A COMPLICATION OF FUNGAL SINUSITIS AND EXTENSIVE POLYPOSIS - Haq, Anwaar ul; Abbas, Shujaat; Ayub, M. Waqas; Asim, Umar; Shabbir, Asad (Pakistan Armed Forces Medical Journal, 2008)
Nasal polypi are non neoplastic masses of oedematous and pedunclated nasal and / or sinus mucosa. The manifestation of nasal polypi depends on the size of the polyp. Small polypi may not produce symptoms and may be identified only during routine ENT examination. Symptomatic polypi can cause nasal obstruction, postnasal discharge, dull headaches, snoring, and rhinorrhea. Massive polyposis or a single large polyp (eg, antraochoanal polyp that obstructs the nasal cavities and/or nasopharynx) can cause obstructive sleep symptoms and chronic mouth breathing. Rarely, the massive polyposis can alter the craniofacial structures and cause proptosis, hypertelorism, and diplopia which was seen in